The effect of projectile travelling at hypervelocity onto solid metal target - Nur Afifah BT Sabar (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This project is about to study the effect of projectile travelling at hypervelocity onto solid metal target. The method is used to control the projectile speed by using explosion in different mass of commercial explosive as an explosion material. The amount of explosive will give impact to projectile to accelerate at hypervelocity and hit the target after explosion happend. The parameter setting such as amount of explosive, material and shape of projectile, material of solid metal target and shaped charge play an important role to control the pressure after an explosion.